Answer:A
Step-by-step explanation:
Answer:
<h2>s = 8 cm</h2>
Step-by-step explanation:
For a square, P = 4s, where s is the length of one side.
Thus, 32 cm = 4s, and s = 8 cm
Answer:
m+g
40
12m + 14g
250
Step-by-step explanation:
Jordan is paid $12 per hour for mowing lawns and $14 per hour for planting gardens.
Let m represents the number of hours mowing lawns and g represents the number of hours planting gardens.
He can work a maximum of 40 hours per week, and would like to earn at least $250 this week.
Then, the system of the inequality becomes
m+g
40
12m + 14g
250
It's just an estimate. There's no telling how close it is.
To estimate using just the information in the table,
ASSUME that the average of all the students in each
slot is the average time of that slot.
I know that's confusing. I can't think of a better way to say it,
so here are two examples of what I mean. Look at the table:
-- 6 students said that they spent between 0 and 30 minutes.
ASSUME that those 6 students averaged 15 minutes each.
-- 21 students said that they spent between 60 and 90 minutes.
ASSUME that those 21 students averaged 75 minutes each.
So, when you add up the times for all 50 students, you'll have
(6 x 15 min) + (14 x 45 min) + (21 x 75min) + (9 x 105 min) =
When you total up all those times, divide it by 50 to estimate
the average per student.
Remember ... it's only an estimate.
If the first group had 1 student that spent 2 minutes, and
the other 5 of them spent 29 minutes, then it won't work.
But you'll never know.
<u><em>subsitution</em></u> means subsituteing something for another and getting the answer
the way to do this is to get an easy equation and make it equal to only one placeholder so
y=2x
so you can subsitute y for 2x anywhere you see a y
3x+y=5
subsitutute
3x+2x=5
5x=5
divide both sides by 5
x=1
subsitute
y=2(1)
y=2
<u><em>elimination</em></u> is when you elimintate one of the terms by adding the equations together and canceling som of them out
so y=2x
subtract y from both sides
0=2x-y or 2x-y=0
add this to the second equation
3x+2x+y-y=0+5
5x=5
divide both sides by 5
x=1
subsitute
y=2(1)
y=2
x=1
y=2